Single‐Electron Transmetalation: Synthesis of 1, 1‐Diaryl‐2, 2, 2‐trifluoroethanes by Photoredox/Nickel Dual Catalytic Cross‐Coupling. Issue 1 (25th November 2015) - Ryu, DaWeon; Primer, David N.; Tellis, John C.; Molander, Gary A.
Abstract: Novel methods for the incorporation of fluorinated subunits into organic frameworks are important in pharmaceutical, agrochemical, and materials science applications. Herein, the first method for the cross‐coupling of benzylic α‐trifluoromethylated alkylboron reagents with (hetero)aryl bromides is achieved through application of a photoredox/nickel dual catalytic system. The harsh conditions and high temperatures required by conventional Suzuki‐coupling protocols are avoided by exploitation of an odd‐electron pathway that permits room temperature transmetalation of these recalcitrant reagents. This method represents the first direct and general route for the synthesis of unsymmetrical 1, 1‐diaryl‐2, 2, 2‐trifluoroethanes, thereby providing efficient access to a previously unexplored chemical space. Abstract : Fluorination : A method for the cross‐coupling of benzylic α‐trifluoromethylated alkylborons with (hetero)aryl bromides has been achieved through application of a photoredox/nickel dual catalytic system. The harsh conditions and high temperatures required by conventional Suzuki‐coupling protocols are avoided by exploitation of an odd‐electron pathway that permits transmetalation of these recalcitrant reagents at room temperature (see scheme).